Amalan program intervensi awal kanak-kanak autistik mengikut perspektif ibu bapa - Liew, Ping Yee; Manisah Mohd. Ali (penerbit ukm, 2008)
The purpose of this study is to explore parents’ perspective on the usage of the types of intervention, service delivery and family involvement in the early intervention program received by autistic children. Data were obtained through questionnaires and interview. Questionnaires were distributed to 50 parents of autistic child aged 2 to 8 years old from five different autistic or learning disabilities centres. Three out of these parents were randomly chosen to be the interview subjects. Data was descriptively analyzed using percentages while the qualititative data were trancribed verbatimly. The results showed that speech therapy is the kind of intervention that most autistic children received. There were changes in the development of the autistic child as a result of intervention. The results also showed that there is a lack of consistency in service delivery between the services delivered by centers and service practitioners. The results too indicated that in most cases only mothers were involved in the early intervention programme. This study has implication on the service planners and parental involvement in the intervention programs.